Forest conditions, objectives and problems in the Pacific area. (Standing Committee on Forest Resources in the Pacific Area, 1950)
An abstract of nine reports submitted to the Standing Committee on Forest Resources in the Pacific Area for the Eight Pacific Science Congress.